1994
DOI: 10.1038/hdy.1994.32
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of a predatory beetle: the importance of gene flow for intertrophic level interactions

Abstract: Migration and gene flow of natural enemies play an important role in the stability of predator-prey interactions and community organization in both natural and managed systems. Yet, relative to that of their herbivorous insect prey, the genetic structure of natural enemy populations has been little studied. We present evidence that populations of the predatory coccinellid beetle Coleomegilla maculata (Coleoptera: Coccinellidae), are not genetically subdivided and that levels of gene flow among these population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Nault and Kennedy (2000) reported that migration occurs among several crops over the course of a season. Coll et al (1994) used allozyme frequencies to estimate gene ßow among populations and concluded that C. maculata is highly mobile. Thus, these insects may be freely moving among treatments even where plots are quite large, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nault and Kennedy (2000) reported that migration occurs among several crops over the course of a season. Coll et al (1994) used allozyme frequencies to estimate gene ßow among populations and concluded that C. maculata is highly mobile. Thus, these insects may be freely moving among treatments even where plots are quite large, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Price (1980) suggested that population subdivision is a major consequence of the parasitic lifestyle and should be typical for both parasitoids and phytophagous insects. Population subdivision has been demonstrated for many species of phytophagous insects, but fewer studies have been conducted for natural enemies such as parasitoids (ColI et al 1994). Specialist paras itoids may be more likely to exhibit population subdivision given that they usually have lower population sizes than their hosts (Godfray 1994).…”
Section: Comparison Of Parasitoid and Host Geographic Structuresmentioning
confidence: 99%
“…Predatory lady beetles (Coleoptera: Coccinellidae) are the only natural enemies whose population structure has been studied extensively (Krafsur et al, 1992(Krafsur et al, , 1995Steiner & Grasela, 1993;Coll et al, 1994). These studies employed allozyme electrophoresis to examine gene flow and the main conclusion drawn from each study was that the lady beetle population was not subdivided, even between states in some cases.…”
Section: Discussionmentioning
confidence: 99%